A Targeted Genetic Association Study of the Rare Type of Osteomyelitis. (March 2020) - Yahara, H.; Horita, S.; Yanamoto, S.; Kitagawa, Y.; Asaka, T.; Yoda, T.; Morita, K.; Michi, Y.; Takechi, M.; Shimasue, H.; Maruoka, Y.; Kondo, E.; et al.
Chronic nonbacterial osteomyelitis is a rare bone disorder that can be found in the jaw. It is often associated with systemic conditions, including autoimmune deficiencies. However, little is known about how the genetic and immunologic background of patients influences the disease. Here, we focus on human leukocyte antigen (HLA), killer cell immunoglobulin-like receptors (KIRs), and their specific combinations that have been difficult to analyze owing to their high diversity. We employed a recently developed technology of simultaneous typing of HLA alleles and KIR haplotype and investigated alleles of the 35 HLA loci and KIR haplotypes composed of centromeric and telomeric motifs in 18 cases and 18 controls for discovery and 472 independent controls for validation. We identified an amino acid substitution of threonine at position 94 of HLA-C in combination with the telomeric KIR genotype of haplotype tA01/tB01 that had significantly higher frequency (>20%) in the case population than in both control populations. Multiple logistic regression analysis based on a dominant model with adjustments for age and sex revealed and validated its statistical significance and high predictive accuracy (C-statistic ≥0.85). Structure-based analysis revealed that the combination of the amino acid change in HLA-C and the telomeric genotype tA01/tB01 could be associated with lower stability of HLA-C. This is the first case-control study of a rare disease that employed the latest sequencing technology enabling simultaneous typing and investigated amino acid polymorphisms at HLA loci in combination with KIR haplotype.